2022
DOI: 10.2174/1570159x19666210908163839
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial Genes in Neurodegenerative Disorders

Abstract: : Mitochondrial disorders are clinically heterogeneous, resulting from nuclear gene and mitochondrial mutations that disturb the mitochondrial functions and dynamics. There is a lack of evidence linking mtDNA mutations to neurodegenerative disorders, mainly due to the absence of noticeable neuropathological lesions in postmortem samples. This review describes various gene mutations in Alzheimer's disease, Parkinson's disease, Amyotrophic Lateral Sclerosis, Multiple Sclerosis, and Stroke. These abnormalities, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 119 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…If a certain heteroplasmy threshold is exceeded, mitochondrial homeostasis can be impaired, subsequently leading to impairments similar to those seen in primary mitochondrial disease and ultimately to cell death [40] (see Figure 2). There is strong experimental evidence that genetic variations in mtDNA increase with age, which also translates to our pathophysiological understanding of the development of neurodegenerative diseases [41]. It has also been shown that the mtDNA mutation rate accelerates with higher age which is especially relevant to postmitotic neurons [42].…”
Section: A Primer On Mitochondrial Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…If a certain heteroplasmy threshold is exceeded, mitochondrial homeostasis can be impaired, subsequently leading to impairments similar to those seen in primary mitochondrial disease and ultimately to cell death [40] (see Figure 2). There is strong experimental evidence that genetic variations in mtDNA increase with age, which also translates to our pathophysiological understanding of the development of neurodegenerative diseases [41]. It has also been shown that the mtDNA mutation rate accelerates with higher age which is especially relevant to postmitotic neurons [42].…”
Section: A Primer On Mitochondrial Biologymentioning
confidence: 99%
“…Even though mtDNA alterations have been observed in physiological aging, the increased amount of mtDNA rearrangements and deletions in PD patients suggest a certain disease specificity [58]. Accordingly, SN-related mtDNA deletions and copy number variations are more common in PD than in patients with other neurodegenerative diseases (e.g., Alzheimer's disease (AD)) [41]. PD patients are thus more likely to accumulate mtDNA mutations particularly in dopaminergic neurons.…”
Section: The Role Of Mitochondrial Dna Deletions and Copy Number Variations In Pdmentioning
confidence: 99%
“…High rates of mutations and mitochondrial damage have been documented in the context of AiN 85,86 and numerous neurodegenerative diseases. 87 Due to its experimental flexibility, advanced and wellcharacterized neurocircuitry, and the availability of an unmatched genetic toolbox, the fruit fly is widely used as (1) a model for neurodegenerative diseases; (2) for toxicologic studies; and (3) for genetic studies and can be arguably considered the ideal model to test the hypothesis that AiN is a quantitative trait. Two models were used to explore the pharmacogenomics of the interactions of isoflurane with "fragile" brains: (1) the brain affected by neurodegeneration using a fly model of LS and (2) the injured brain using a fly Traumatic Brain Injury (TBI) model.…”
Section: Genetic Determinants Of Collateral Anesthetic Pharmacodynamicsmentioning
confidence: 99%
“…Neurodegenerative disorders characterized by a gradual reduction of nerve cell functions or structure that may lead to neuron death. Neurodegenerative diseases included Huntington's disease (HD), Parkinson's disease (PD),Alzheimer's disease (AD), and amyotrophic lateral sclerosis (ALS) [1]. These disorders are considered incurable, and they cause a progressive decline in health to the point that neurons die.…”
Section: Introductionmentioning
confidence: 99%